2020
DOI: 10.3103/s0096392520040136
|View full text |Cite
|
Sign up to set email alerts
|

Functional Activity of Aryl Hydrocarbon Receptor in Human Osteosarcoma Cell Cultures

Abstract: Остеогенная саркома -агрессивная злокачественная опухоль костной ткани, возникающая в молодом возрасте (10-19 лет) и, как правило, заканчивающаяся фатально. Арил-гидрокарбоновый рецептор человека (Aryl Hydrocarbon Receptor, AHR) -лиганд-зависимый транскрипционный фактор, который связан с детоксикацией ксенобиотиков и канцерогенезом. Известно, что некоторые лиганды AHR входят в состав фармацевтических препаратов, применяемых в онкотерапии. Однако в мировой литературе мало работ, посвященных исследованию последс… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Their findings demonstrated functional AhR activity in all cell lines but with variable activation patterns of target genes in response to ligand stimulation. 97 Yang et al demonstrated that treatment of the MG-63 osteosarcoma cell line led to the degradation of AhR expression via activation of the AhR signaling pathway 98 . They observed elevated levels of cyclooxygenase-2 and receptor activator of nuclear factor-κB ligand at both protein and mRNA levels after 24 and 72 hours of TCDD treatment.…”
Section: Ahr Role In Bone Homeostasismentioning
confidence: 99%
“…Their findings demonstrated functional AhR activity in all cell lines but with variable activation patterns of target genes in response to ligand stimulation. 97 Yang et al demonstrated that treatment of the MG-63 osteosarcoma cell line led to the degradation of AhR expression via activation of the AhR signaling pathway 98 . They observed elevated levels of cyclooxygenase-2 and receptor activator of nuclear factor-κB ligand at both protein and mRNA levels after 24 and 72 hours of TCDD treatment.…”
Section: Ahr Role In Bone Homeostasismentioning
confidence: 99%